Virtual currency (Bitcoin), legal adaptation and the ruling on dealing with it - زعين محمد جمال; محمد عبد الباسط جاسم (Journal of Legal Sciences, 2021)
In a world that is accelerating day after day in the context of technical globalization, this speed appeared in the issue of electronic currency trading, which is linked to banks all over the world, then the virtual bitcoin coin appeared, and its place is the Internet, and contains an encryption system that is not related to the center or the bank. This coin spread widely and was invested by major companies. In legislative terms, this currency was not granted its right or proper organization, while jurisprudence was dealt with in a simple way, as this coin needs further studies. This research explains the challenges arising from the concept of this currency to determine the legal nature that enters under it, in addition to discussing the possible legal classification of bitcoin, that this currency needs regulations to protect users and benefit from its advantages and avoid risks.